Enriching BIM with Unmanned Aerial Systems Data for Enhancing Construction Management Operations - Rahnamayiezekavat, Payam; Mourad, Mohamed; Mostafa, Sherif; Moon, Sungkon; Senaratne, Sepani (Sustainability (Switzerland), 2022)
The use of an unmanned aerial system (UAS) in construction project management (CPM) is an emerging methodology aimed at improving the performance of project management practices. Despite the different functions that an UAS offers, which are well covered in various sources ranging from isolated exploratory works to ad hoc case studies, construction practitioners still demonstrate little interest in UAS technology. The underwhelming interest is rooted in a lack of an understanding of the value of the data collected using UASs and their potential to enrich Building Information Modelling (BIM). This research presents the details of the UAS developed to check the accuracy of work performed, along with the generation of the corresponding progress payment reports as well as referencing and tracking information in real time, for a residential project. This study also discusses combining the data generated from the UAS and 5D BIM to develop a smart construction site. The UAS–BIM combination enables the project stakeholders to be fully informed of the work’s progress and quality to avoid mistakes that could lead to extra costs and delays. The paper identified the main obstacles to applying the UAS via interviews with the project managers and tradespersons involved in the selected project. Assuredly, a digital culture is essential for a smart construction site to shift the project team from a passive data user to a more proactive analyzer to improve performance and site safety. Other obstacles include ethical reservations, legal requirements, liability risks, weather conditions, and the continuation of using an UAS in non-open-air construction environments.
Keywords: building information modelling; construction project management; digital culture; progress report; smart construction site; unmanned aerial system